2021
DOI: 10.1038/s41562-021-01135-3
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of 371 genetic variants for age at first sex and birth linked to externalising behaviour

Abstract: Age at first sexual intercourse (AFS) and age at first birth (AFB) have implications for health and evolutionary fitness. In this genome-wide association study (AFS, N=387,338; AFB, N=542,901), we identify 371 SNPs, 11 sex-specific, with a 5-6% polygenic score (PGS) prediction. Heritability of AFB shifted from 9% [CI=4-14] for women born in 1940 to 22% [CI=19-25] in 1965. Signals are driven by the genetics of reproductive biology and externalising behaviour, with key genes related to follicle stimulating hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 85 publications
(120 reference statements)
5
79
0
Order By: Relevance
“…CADM2 mediates synaptic plasticity and is enriched in the frontal cortex and striatum, which are regions that regulate reward and inhibitory processes. We and others have implicated this gene in traits that may underlie disinhibition in humans, supporting the observed genetic correlations between impulsivity and personality (8), educational attainment (9), cognition (10), risk-taking (11), substance use (4,10,1215), externalizing psychopathology (16), neurodevelopmental disorders (17,18), physical activity (23), reproductive health (20,21), metabolic traits (19), and BMI (22), among others (see GWAS Catalog www.ebi.ac.uk/gwas/). Cadm2 knockout mice have previously been assessed for body weight and energy homeostasis (24) but have never been behaviorally characterized for measures of impulsivity or related behaviors.…”
Section: Introductionsupporting
confidence: 67%
“…CADM2 mediates synaptic plasticity and is enriched in the frontal cortex and striatum, which are regions that regulate reward and inhibitory processes. We and others have implicated this gene in traits that may underlie disinhibition in humans, supporting the observed genetic correlations between impulsivity and personality (8), educational attainment (9), cognition (10), risk-taking (11), substance use (4,10,1215), externalizing psychopathology (16), neurodevelopmental disorders (17,18), physical activity (23), reproductive health (20,21), metabolic traits (19), and BMI (22), among others (see GWAS Catalog www.ebi.ac.uk/gwas/). Cadm2 knockout mice have previously been assessed for body weight and energy homeostasis (24) but have never been behaviorally characterized for measures of impulsivity or related behaviors.…”
Section: Introductionsupporting
confidence: 67%
“…A recent study suggested that this trait was associated with hundreds of genetic loci and older age at first birth was associated with longevity and decreased incidence of type 2 diabetes and cardiovascular disease. 26 In combination with their findings, we assumed that a proper delay of first sexual intercourse potentially decrease CSVD burden in later life. Another exposure, higher overall health rating, surprisingly turned out as a risk exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Other research has examined sexual, fertility and reproductive behavior, including an initial study led by sociologists and demographers studying the age at first birth and number of children ever born (Barban et al 2016). A recent follow-up to this study found 371 loci related to age at first sex and birth (Mills et al 2021), which were linked to externalizing behavior. A companion study of number of children ever born in contemporary populations traced evolutionary patterns from ancient genome data, which we return to shortly (Mathieson et al 2020).…”
Section: Contemporary Empirical Sociogenomic Researchmentioning
confidence: 95%
“…This is one of the areas where synergies can be gained for sociological theory and empirical research by combining assumptions on agency, such as assumptions on rational choice, with insights from genetics. Specifically, this includes progress in understanding behaviors that seem counter-intuitive from an agency perspective, at least at first sight, such as behaviors with detrimental outcomes like obesity or opioid addiction, and more generally behaviors often referred to in the psychological literature as lack of self-control, risk-taking, externalizing behavior or behavioral disinhibition (Mills et al 2021).…”
Section: Rational Choice Agency-based Theoriesmentioning
confidence: 99%
See 1 more Smart Citation